1997
DOI: 10.1080/02705060.1997.9663554
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silver Carp Density on Zooplankton and Water Quality: Implications for Eutrophic Lakes in China

Abstract: We examined the responses of zooplankton community, water transparency, chlorophyll a-and nutrients to manipulation of density of silver carp (Hypophthyalmichthys rnolitrix) in an one-way factorial experiment using enclosures placed in Donghu (East Lake, 30" 33' N, 114" 23' E), located in Wuhan, P. R. China. Enclosures (18.75 m3) were treated with four silver carp densities, 0,81,225,485 g/m2. Total zooplankton abundance (excluding nauplii and rotifers except for Asplanchna sp.) and the mean size of dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
(16 reference statements)
3
12
0
Order By: Relevance
“…In the absence of grazing by planktivorous fish, enhanced crustacean grazing suppressed the small algae that are vulnerable to crustaceans, and inedible algae like large colony, toxic cyanobacteria species or those with gelatinous sheaths flourished (LYNCH andSHAPIO, 1981 andVANNI, 1987). In our experiment as well as in the experiments carried out by FUKUSHIMA et al (1999, EXP2) andWU et al (1997), the initial dominant phytoplankton were nanophytoplankton. Increased crustaceans in the fishless enclosures caused reduction of small phytoplankton, but did not cause an outburst of inedible algae like cyanobacteria.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In the absence of grazing by planktivorous fish, enhanced crustacean grazing suppressed the small algae that are vulnerable to crustaceans, and inedible algae like large colony, toxic cyanobacteria species or those with gelatinous sheaths flourished (LYNCH andSHAPIO, 1981 andVANNI, 1987). In our experiment as well as in the experiments carried out by FUKUSHIMA et al (1999, EXP2) andWU et al (1997), the initial dominant phytoplankton were nanophytoplankton. Increased crustaceans in the fishless enclosures caused reduction of small phytoplankton, but did not cause an outburst of inedible algae like cyanobacteria.…”
Section: Discussionsupporting
confidence: 49%
“…Experimental design and descriptions of the enclosures are similar to those given by WU et al (1997). Eight polyethylene enclosures (each 2.5 × 2.5 m by 2 m depth) were hung from steel pipes which were mounted at the bottom.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased fish density may increase the possibility of fish coming in contact with sediment on the lake bed and consequently promote the release of nutrients from the sediment. The results from the Lake Taihu enclosures are consistent with the study conducted in eutrophic Lake Donghu enclosures by Wu et al (1997).…”
Section: Discussionsupporting
confidence: 80%
“…In the Lake Taihu enclosures, the removal of algae by silver carp at 35 and 70 g m −3 resulted in a particularly noticeable reduction in phosphorus, primarily in particulate form, whereas dissolved phosphorus was evident at similar levels in different treatments. Wu et al (1997) also found that water had the lowest TP values when silver carp biomass was 81 g m −3 (medium biomass), whereas TN did not differ between fish enclosures and non-fish enclosures. Cui et al (2004) have also found that silver carp are more effective at removing phosphorus than nitrogen.…”
Section: Discussionmentioning
confidence: 88%